PP135 Stakeholder Involvement In A Health Technology Assessment Of Hyperhidrosis. (2017) - Wade, Ros; Rice, Stephen; Moloney, Eoin; Stoniute, Julija; Layton, Alison; Levell, Nick; Stansby, Gerard; Jones-Diette, Julie; Llewellyn, Alexis; Wright, Kath; Craig, Dawn; Woolacott, Nerys
Abstract : INTRODUCTION: Hyperhidrosis is characterized by uncontrollable excessive sweating, which occurs at rest, regardless of temperature. Symptoms can significantly affect quality of life. There is substantial variation in the secondary care treatment of hyperhidrosis and uncertainty regarding optimal patient management. The objective of the Health Technology Assessment (HTA) was to review the evidence and establish the expected value of undertaking additional research into effective interventions for the management of primary hyperhidrosis in secondary care. Capturing the perspectives of patients and clinicians treating hyperhidrosis was an important part of the research. METHODS: The assessment included a systematic review and economic model, including value of information analysis. Patients, dermatologists, a vascular surgeon and a specialist nurse (who set up the UK Hyperhidrosis Support Group) provided advice at various stages, including at an end-of-project workshop, to help interpret results and prioritize research recommendations. RESULTS: Patient and clinician advisors were unsurprised by the finding that there is evidence of a large effect of botulinum toxin injections on axillary hyperhidrosis symptoms in the short to medium term; there was consensus amongst patients and clinicians that botulinum toxin injections were very effective. The advisors agreed that a trial of botulinum toxin injections (plus anesthetic) versus iontophoresis for palmar hyperhidrosis would be useful. Patients and clinicians were happy with the sequence of treatments identified as being cost effective for axillary hyperhidrosis: iontophoresis, botulinum toxin injections, anticholinergic medication, curettage, endoscopic thoracic sympathectomy. All patients agreed that the Hyperhidrosis Quality of Life index (HidroQoL©) tool was superior to other commonly used tools for assessing quality of life in hyperhidrosis. CONCLUSIONS: Patients and clinicians considered the key findings of the systematic review and economic analyses to be appropriate. Advisors advocated a trial of botulinum toxin injections (plus anaesthetic) versus iontophoresis for palmar hyperhidrosis. Patients preferred the HydroQoL® tool over other commonly used quality of life tools in hyperhidrosis research.